Intelligent Connected Technology for Campus Vehicle Applications: A Review - Wang, Ruoxi (Computers and Artificial Intelligence, 2025)
Intelligent connected technology (ICT), a product of the deep integration of artificial intelligence (AI), the Internet of Things (IoT), communication technologies, big data, and autonomous driving, aims to increase transportation safety, efficiency, and comfort through synergistic “intelligence” and “connectivity.” This synergy enables real-time information interaction and collaborative decision-making among vehicles, road infrastructure, users, and cloud platforms, ultimately fostering a smarter, greener, and more efficient transportation system. With the increasing application of ICT in confined environments, university campuses, as typical microcosms of urban settings, are witnessing a transformation in vehicle usage demands—shifting from mere commuting to social, collaborative, and scenario-integrated needs. This review focuses on the closed-campus context, investigating the mechanisms through which ICT drives the socialization, collaboration, and scenario fusion of campus vehicle use, thereby providing theoretical support for tailoring technology to campus-specific scenarios. Specifically, we synthesize research progress across three critical dimensions: social connectivity, fleet collaboration, and scenario integration. Employing a critical analysis approach, we examine the methodological designs and conclusion applicability of existing studies, highlight their limitations, and substantiate our arguments with empirical cases from pilot initiatives at Chinese universities. Moving beyond the prevailing singular focus on “technical functionality,” this paper pioneers a “demand-technology-scenario” triadic interactive perspective to reveal the adaptation gap between technology and social needs in campus mobility. On the basis of an analysis of 35 literature sources, primarily from the last five years, we identify significant shortcomings in technology-scenario adaptation. Future efforts should focus on interdisciplinary integration, targeted innovation, and application scenario expansion to promote the deep integration of ICT with campus vehicle ecosystems.